Forecast the Adult Learning Education in Kuwait through 2024 - Al-Ajmi, Rasha Mhdi; Al-Tuwaijri, Sheikha Ibrahim; Al-Otaibi, Fatima Mutlaq; Al-Rashidi, Ghazi (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the predictive values of the secular trend for the next five years of the time series to the most important educational factors in Literacy and Adult Learning Education in Kuwait. Also, it aimed to compare between growth rate on the secular trend of the time series towards the most important educational factors at Literacy and Adult Learning Education at the different phases. Time series was used to analyze Literacy and Adult Learning Education’s statistics; which were taken from Ministry of Education in Kuwait, from 2014 to 2019. The study showed several results such as most of the educational factors’ growth rates were low. In addition, it appeared that most of the predictive values from 2020 to 2024 were degreased. The growth rate for the total centers for adult learning was- 2.7%; whereas, it was- 3.7% for classes. Also, the growth rate for the total of students was- 1.9%. The last but not the least, the growth rate for the total of teachers was the lowest which was- 6.0%. Several recommendations and suggestions were given based on the results of this study.